Characterization of CD8 T cell responses in Mycobacterium Tuberculosis infection - Moshi, Noell Dominika (Division of Immunology, 2015)
The aim of this project was to compare the breadth and magnitude of CFP10 and ESAT6-specific CD8 T cell responses in individuals with latent Mycobacterium tuberculosis (MTB) infection (LTBI) and active TB disease, and further define MTB-specific CD8 T cell phenotypes associated with latent infection and active disease. Ex vivo IFN? Elispots and proliferation assays were used to identify immunodominant ESAT6 and CFP10 15mer peptides targeted by CD8 T cells in LTBI and TB donors. A multiparameter flow cytometry panel was designed and optimized to assess turnover, susceptibility to apoptosis and terminal differentiation/senescence in CD8 T cells from TB and LTBI donors. Bcl-2, Ki67,CD95, CD57, CD127 and IFNγ were thus measured in each group.